Enciclopédia da música em Portugal no século XX - Salwa Castelo-Branco (Temas e Debates, 2010)
1.º vol.: "A-C", 326 p.; 2.º vol.: "C-L", 327-698 p.; 3.º vol.: "L-P", 699-1070 p.; 4.º vol.: "P-Z", 1071-1455 p.